PERAN ORANGTUA DALAM MEMBIMBING MENYIKAT GIGI DENGAN KEJADIAN KARIES GIGI ANAK PRASEKOLAH - Ana Suciari; Yuni S. Arief; Praba D. Rachmawati (Universitas Airlangga, 2016)
Introduction : Dental caries is a pathological process in the form of limited damage to the tissue of the tooth, strating from enamel to dentin. Dental caries or cavities can be seen when it forms openings or holes which can be seen by naked eye and has a change of color to brown and black. Dental caries occurs because of demineralization of the interaction of bacteria on the tooth surface. Bacteria are acidic so within a certain time period, the acid will damage the tooth enamel and cause cavities. This research aimed to find the correlation between parents’ role in guiding to brush teeth and dental caries case in preschool children at TK Az-Zahra Gedangan Sidoarjo.Method : The research design used was descriptive analysis with cross sectional. The population of this research were parents (mothers) and student of TK Az Zahra Gedangan Sidoarjo with the number of sample was 26 respondents. The independent variable was parents’ role in guiding to brush teeth, while the dependent variable was dental caries case. The instruments used to collect data were questionnaires and observation sheets. The data was analyzed by using Chi Square data analysis with significance level α<0,05.Result : The results showed that there was no correlation between parents’ role in guiding to brush teeth and dental caries case in preschool children (p=0,395). Discussion : Given these findings, it could be concluded that there was no correlation between parents’ role in giving guide to toothbrushing and dental caries in preschool children. Thus, parents should increase their role in guiding children to brush teeth regularly, because children at that age needed intensive guide and supports from parents to minimize dental caries case